Stress field solution for strip loaded reinforced concrete blocks. (15th September 2018) - Markić, Tomislav; Kaufmann, Walter; Amin, Ali
Highlights: The fundamental mechanical behaviour of partially loaded areas is discussed. A review of previous theoretical work reveals a remarkable knowledge gap. A stress field for reinforced concrete blocks under strip loading is presented. A comparison with the available experimental results shows a good correlation. A step towards mechanically based design rules for partially loaded areas is made. Abstract: This paper aims at contributing to a better understanding of the physical-mechanical behaviour of partially loaded areas in reinforced concrete. Following a review of the current state of the art on this topic, which includes a description of the mechanical behaviour and existing predictive models, a remarkable knowledge gap in this standard problem is revealed. A new stress field solution for reinforced concrete blocks under strip loading is developed herein which is based on the lower-bound theorem of limit analysis and adopts a modified Coulomb failure criterion for concrete. Contrary to existing empirical design rules, the new mechanical model consistently accounts for the behaviour of concrete under multiaxial compression as well as the favourable effect of transverse reinforcement. While a comparison of the ultimate loads predicted using the new stress field solution shows a good correlation with the available test data, further experiments are required particularly for the validation of the predicted higher resistances of heavily confined areas as compared to existing design rules.